Primary cervical hydatid cyst - Olivera Whyte, Lucila M.; García Mazaira, Guadalupe; Eremeeff, Ariel; Omeñuk, Gastón; Confalonieri Quiroz, Marcelo; Cazalá, Agustina (Revista Argentina de Cirugía, 2021)
Cervical echinococcosis is a rare disease, even in endemic areas. The lesions usually present as painless slow-growing cystic lesion. We report the case of a 19-year-old female patient with a cystic lesion in the central cervical region that was initially interpreted as a thyroglossal duct cyst. The diagnosis should be suspected when the epidemiology is consistent, and ultrasound is the imaging method of choice. The sensitivity of serologic tests is low in extrahepatic locations. Surgery is the treatment of choice and the administration of albendalzole before surgery is indicated. The cyst must be handled with care to avoid rupture and leakage of cyst contents, which can cause anaphylaxis, recurrence and multiple echinococcosis. In patients with high surgical risk, medical treatment alone may be the option.